Caenorhabditis elegans as an emerging model system in environmental epigenetics. (9th August 2018) - Weinhouse, Caren; Truong, Lisa; Meyer, Joel N.; Allard, Patrick
Abstract : The roundworm Caenorhabitis elegans has been an established model organism for the study of genetics and developmental biology, including studies of transcriptional regulation, since the 1970s. This model organism has continued to be used as a classical model system as the field of transcriptional regulation has expanded to include scientific advances in epigenetics and chromatin biology. In the last several decades, C. elegans has emerged as a powerful model for environmental toxicology, particularly for the study of chemical genotoxicity. Here, we outline the utility and applicability of C. elegans as a powerful model organism for mechanistic studies of environmental influences on the epigenome. Our goal in this article is to inform the field of environmental epigenetics of the strengths and limitations of the well‐established C. elegans model organism as an emerging model for medium‐throughput, in vivo exploration of the role of exogenous chemical stimuli in transcriptional regulation, developmental epigenetic reprogramming, and epigenetic memory and inheritance. As the field of environmental epigenetics matures, and research begins to map mechanisms underlying observed associations, new toolkits and model systems, particularly manipulable, scalable in vivo systems that accurately model human transcriptional regulatory circuits, will provide an essential experimental bridge between in vitro biochemical experiments and mammalian model systems. Environ. Mol. Mutagen. 59:560–575, 2018. © 2018 Wiley Periodicals, Inc.